Organized Institutions of Medieval Hungarian Healthcare: the Crusader Knights’ Orders - Falus, Orsolya (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
In the Middle Ages, the hospitaller Crusader knight orders were church communities established on the basis of a rule, similar to the monastic orders, whose members, in addition to the triple oath of poverty, chastity and obedience, also undertook to nurse the sick and needy. These confraternities were special “non-profit organizations” created within the Jewish-Christian cultural circle, which, among their various “public benefit” activities, primarily aimed to care for the sick and ensure the peace of God (Treuga Dei). The paper presents the rules of St. Benedict and St. Augustine as the bases of the “memorandums of association” of these organizations, as well as medieval Hungarian medicine and their place and role in it.